DIVERSITY OF AQUATIC INSECTS IN RICE FIELD, PHITSANULOK PROVINCE - Phalee, Waraporn; Sittikul, Sarawut; Phalee, Anawatch (Life Sciences and Environment Journal, 2024)
The study aims to study the diversity of aquatic insects in rice fields in Phitsanulok Province. A total of 20,984 specimens of aquatic insects were collected by using a sweep net. These aquatic insects were classified into three main orders: Odonata, Hemiptera, and Coleoptera, comprising 12 families. The highest number of insects was found in the order Hemiptera, with the family Notonectidae being the most abundant. Following that were the orders Odonata and Coleoptera. The analysis of the Shannon-Wiener’s Index (H’) and evenness (J’) for all collected aquatic insects in the rice fields showed values of 2.800 and 0.281, respectively. Among the districts in Phitsanulok Province, Mueang Phitsanulok had the highest biodiversity and evenness values, with 2.817 and 0.283, respectively. The month with the highest biodiversity and evenness values was July, with values of 2.834 and 0.285, respectively. The results of this study can be used as baseline data for planning and managing rice fields sustainably to preserve biodiversity in the future.